Adaptive Reuse of Vacant Commercial Buildings into Urban Affordable Housing - Adam, Afifah Mohd. (MAJ - Malaysia Architectural Journal, 2025)
Due to rapid urbanization and uncontrollable city developments has leads to abandonment and deterioration of old commercial buildings, impacting property values, public safety, and the environment. However, Kuala Lumpur is experiencing a decreasing population rate, with housing either too expensive or in terrible condition, forcing the working class to move to suburb with more affordable housing options. Kuala Lumpur City Hall (KLCH) introduced a project called ‘Perumahan Bandar’ by using adaptive reuse strategy. Past research has shown that sustainability can be achieved by integrating human needs with the environmental considerations. The purpose of this paper is to identify the opportunities and risks associated with adaptive reuse strategies for converting vacant commercial buildings into affordable housing as a sustainable solution for unoccupied commercial buildings. The method used is multiple case studies and expert interviews to understand the issue of vacant commercial buildings in various contexts and to gather expert opinions on adaptive reuse strategies for addressing empty premises issues in the urban setting. The findings of this paper indicate that the effectiveness of the building adaptive reuse strategy depends on a thorough understanding of its opportunities and risks, which are influenced by the drivers and barriers of the process. The strategy of converting vacant commercial buildings into affordable housing offers a shorter development period, provides sustainable design solution for unused buildings, and enhances community well-being.